Interethnic Workplace Conflict: Reciprocal Perception of Italian and Immigrant Blue-Collar Coworkers - Maria Grazia Monaci (Europe's Journal of Psychology, 2022)
Past research has examined the beneficial effects of contact focusing mainly on the affective dimension of intergroup relationships. Limited research has examined cognitive dimensions, in particular considering at the same time minority and majority group perspectives. This study tested whether contact in a work context relates differentially to the perception of interethnic conflict in Italian (n = 67) and immigrant (n = 40, all male) blue-collar coworkers with the potential mediation of reciprocal stereotypical content (competence and warmth dimensions), interethnic attitudes, perceived discrimination, and whether organizational identification amplifies the effect of contact. Multigroup path analysis revealed that the two stereotype dimensions, warmth and competence, mediate the relationship between interethnic contact and perceived discrimination for Italians, and between organizational identification and perceived conflict for immigrants. Results highlighted an asymmetrical effect of contact on perceived conflict, detrimental and direct for immigrant workers, beneficial and mediate via the outgroup cognitive image for the Italian workers. Findings suggest that a superordinate identity, in terms of organizational identification, may be effective in reducing conflict at the workplace for majority members, whilst a personalized strategy seems to be more suitable for minority members. The theoretical and practical implications of these findings are discussed along with the acculturation perspective.